Assessment of mirror movements in children and adolescents with unilateral cerebral palsy: reliability of the Woods and Teuber scale. (19th January 2021) - Magne, Victoria A; Adde, Lars; Hoare, Brian; Klingels, Katrijn; Simon‐Martinez, Cristina; Mailleux, Lisa; Lydersen, Stian; Elvrum, Ann‐Kristin G
Abstract : Aim: To investigate the inter‐ and intrarater reliability of the Woods and Teuber scale to detect mirror movements in children and adolescents with unilateral cerebral palsy (CP). Method: A convenience sample of children and adolescents with unilateral CP ( n =68; 31 males, 37 females; mean age 12y 2mo, SD 3y 6mo) in Manual Ability Classification levels I to III was recruited from Norway, Australia, and Belgium. Three therapists scored mirror movements according to the Woods and Teuber scale from three video‐recorded tasks at two separate time points. A two‐way, mixed model regression was used to calculate intraclass correlation coefficients (ICCs) reflecting overall inter‐ and intrarater reliability. In addition, ICCs for each hand and task were calculated separately. Results: The overall interrater reliability ICC was 0.90 and the corresponding intrarater reliability ICC was 0.92. The ICCs for each hand ranged from 0.86 to 0.92 and for each task from 0.63 to 0.89. Interpretation: The Woods and Teuber scale shows excellent reliability for scoring mirror movements in children and adolescents with unilateral CP. The assessment is easy to administer with no need for specific equipment and scoring can be determined from short video recordings, making it a feasible instrument in research and clinical practice.